Policing in the Era of AI and Smart Societies - Jahankhani, Hamid; Akhgar, Babak; Cochrane, Peter; Dastbaz, Mohammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book presents a compilation of collaborations between researchers and practitioners in the fields of policing and cyber criminology, IT law and security, providing a comprehensive overview of current and emerging challenges in law enforcement, AI and Digital Society. The advent of Artificial Intelligence (AI), together with the spread of Internet of Things (IoT) devices, is creating smart societies that are increasingly interconnected. The scope of connectivity, massive rise in the volume of smart devices and growing interfaces between humans and technology, together with the expansion of Big Data and volumetric metadata generated and collated, are driving the cultural change toward Industry 4.0. Therefore, in light of do-it-yourself biohackers trying to become cyborgs, Augmented Humanity (fusion between humans and technology), governments$1 (Butilization of the various technologies (example eHealth), holographic communications, smart cities / smart societies, cryptocurrencies etc., in the era of Industry 4.0 with AI at its core, enhancing their policing models has become a priority for governments. As the patterns of crime, policy and technology are changing in line with smart societies, law enforcement agencies around the world are called upon to formulate future-ready legislative frameworks, rethink crime prevention, investigatory decision making and predictive policing, prevent or mitigate potentially devastating cyber-attacks, and ensure the security of operational capabilities, namely: Command, Control, Communications and Intelligence (C3I). .s
Foreword -- Rethinking Criminal Justice in Cyberspace: The EU E-evidence framework as a new model of cross-border cooperation in criminal matters -- Policing in the era of AI and Smart Societies: austerity; legitimacy and blurring the line of consent -- Behavioral Analytics; A Preventative Means for the Future of Policing -- Securing Transparency and Governance of Organ Supply Chain Through Blockchain -- IoT and cloud forensic investigation guidelines -- Algorithms can predict domestic abuse, but should we let them? -- Tackling teen sexting - policing challenges when society and technology outpace legislation -- Image Recognition in Child Sexual Exploitation Material - Capabilities, Ethics and Rights -- Predictive policing in 2025: A scenario -- Patterns in Policing -- Proposed Forensic Guidelines for the Investigation of Fake News -- Current Challenges of Modern-Day Domestic Abuse.
Keywords: Police; Artificial intelligence; Crime prevention; Policing; Artificial Intelligence; Crime Prevention